2017
DOI: 10.1136/archdischild-2016-311813
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen saturation ranges for healthy newborns within 24 hours at 1800 m

Abstract: There are minimal data to define normal oxygen saturation (SpO2) levels for infants within the first 24 hours of life and even fewer data generalisable to the 7% of the global population that resides at an altitude of >1500 m. The aim of this study was to establish the reference range for SpO2 in healthy term and preterm neonates within 24 hours in Nairobi, Kenya, located at 1800 m. A random sample of clinically well infants had SpO2 measured once in the first 24 hours. A total of 555 infants were enrolled. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 5 publications
3
11
0
Order By: Relevance
“…We recognise that normal saturations can be lower for neonates immediately after birth and can vary by probe location (pre-ductal versus post-ductal). However, studies in similar settings have reported that more than 95% of SpO 2 readings are ≥90% even in the first hours of life (irrespective of probe location) [60].…”
Section: Discussionmentioning
confidence: 97%
“…We recognise that normal saturations can be lower for neonates immediately after birth and can vary by probe location (pre-ductal versus post-ductal). However, studies in similar settings have reported that more than 95% of SpO 2 readings are ≥90% even in the first hours of life (irrespective of probe location) [60].…”
Section: Discussionmentioning
confidence: 97%
“…Gestational age was based on last menstrual period (LMP), and Ballard examination was conducted when LMP was unknown or incongruent with appearance (ultrasonography is rarely available). We determined the prevalence of hypoxaemia, calculated as the number of neonates with pre-or post-ductal SpO 2 below the previously defined local threshold of 89% for healthy term and preterm neonates within 24 h at 1800 m, 31 divided by the total number of neonates admitted during the study period. We determined odds ratios for hypoxaemia and all-cause inpatient death by gestational age, birthweight and clinical risk factors and signs.…”
Section: Methodsmentioning
confidence: 99%
“…Ravert et al ( 21) compared SpO 2 in term infants and premature infants born at altitudes of 1,371-2,484 meters, and found that preterm infants tend to have higher SpO 2 ; however, the authors did not specify the exact gestational age. But, multiple studies (16,22) on healthy late preterm infants and term infants showed that there was no difference in SpO 2 between them after birth.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we only included studies reporting SpO 2 levels during the period from 24 h after birth to before discharge. Studies reporting SpO 2 within 24 h of birth were excluded because SpO 2 levels fluctuate during this period ( 16 ). In a study conducted at sea level on healthy neonates, Toth et al found that the mean post-ductal SpO 2 was 67% at 2 min after birth, but rose gradually over 14 min to reach 95% ( 17 ).…”
Section: Discussionmentioning
confidence: 99%